Audio-Visual Learning Media Based on Digital Literacy on the Topic of the Water Cycle - Kadek Siska Wulandari; Desak Putu Parmiti; I Made Citra Wibawa (Universitas Pendidikan Ganesha, 2023)
The use of digital learning media is currently very necessary. It is related to literacy, literacy skills, and the ability to use technology effectively. This research aims to develop Digital Literacy-Based Audio Visual Learning Media on the Topic of the Water Cycle. This type of research is developed using the ADDIE model. The research subjects were one learning material expert, one learning media expert and one practitioner. The test subjects were 25 fifth-grade elementary school students. Methods of data collection using interviews, questionnaires and tests. The data collection instrument uses a rating scale. The techniques used to analyze the data are descriptive qualitative analysis, quantitative and inferential statistics. The research results are the assessment of the learning design expert, getting a score of 97.5% (very good). The assessment of the learning material expert is 93.3% (very good). The assessment of learning media experts is 97.6% (very good). The results of the teacher's assessment were 95.2% (very good). The assessment results of student responses were 89.5% (very good). The t-test results showed a significant influence between Digital Literacy-Based Audio Visual Learning Media on the learning outcomes of fifth-grade elementary school students. It was concluded that Digital Literacy-Based Audio Visual Learning Media could improve student learning outcomes.